CRITICAL INVESTIGATION INTO THE HEALTHCARE ISSUES FACED BY PATIENTS IN GOVERNMENT HOSPITALS OF BHANDARA DISTRICT - Hisaria, Mohini Laloo; Vyas, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Government hospitals are key to giving healthcare to people who have less access to services in Bhandara district. The research paper analyzes the many problems patients face when trying to access care at Bhandara’s government hospitals. Empirical data was collected by interviewing patients, hospital staff and attendants while giving them questionnaires. The major problems found are inadequate hospitals, a shortage of doctors and nurses, lots of waiting, unwashed conditions, little access to drugs and slow progress resulting from management problems. Factors from the community and economy that affect health care are studied. The results indicate that there are systemic problems that hold back effective public healthcare delivery. At the end of the paper, we suggest steps that can be implemented to increase the quality of services, hold staff accountable and improve how patients feel about government healthcare institutions.